EVALUATE THE SERVICES IN UK HEALTHCARE INDUSTRY AND SUGGEST WAYS FOR BETTER INTEGRATION AND VALUE CO CREATION BETWEEN CUSTOMERS AND SUPPLIERS: A GE HEALTHCARE PERSPECTIVE - Tiwari, Padmanabh (2010)
This work is an effort to understand the various dimensions of service marketing and evaluate them from the perspective of healthcare industry. Furthermore this report will attempt to add the new dimension of service dominant logic in healthcare sector so that organizations such as GE healthcare can capitalize on that and co create value in close cooperation with its customer to increase their business base and gain competitive advantage in a highly demanding healthcare industry. The research conducted in this paper is based on both theoretical and the practical dimensions. The start of this report provides the theoretical dimension by elaborating on the literature whereas the close association with GEHC and the interviews conducted will add the practical and applied dimension to this research work. This amalgamation will help serving the purpose of both the practitioner and the researcher.